Charles Spence Bate: what’s in a name? - Clark, Paul F. (Zootaxa, 2018)
The citation of Charles Spence Bate has become a source of uncertainly in the literature. Indeed, for some taxa his authority is given as “Spence Bate”, whilst others “Bate” e.g. Artemesia longinaris Spence Bate, 1888 compared with Ibacus brevipes Bate, 1888. In order to resolve this inconsistency, a lengthy manual search of selected contemporary journals for the period from ca. 1854 to 1889 was undertaken with special reference to the name Charles Spence Bate being listed alphabetically by family/surname either under “Bate”, “Spence Bate” or “Spence-Bate”. Overwhelming evidence indicated that his family/surname is Bate. Furthermore, as there are a number of carcinologists also with the family name Bate, therefore it is recommended that taxa described by Charles Spence Bate should be referred to as C.S. Bate, for example Artemesia longinaris C.S. Bate, 1888 and Ibacus brevipes C.S. Bate, 1888.